Genotoxic Impurities of N-Nitrosamine in Efavirenze Drug Substance Determined by Using Using RP-HPLC Technique - Sravanthi, A. Devi; Bharath, P.; Kiranmayi, P.; Ramachandran, D. (Recent Developments in Chemistry and Biochemistry Research Vol. 4, 2024)
Aim: The main purpose of the research is to develop an effective, sensitive, economical and simple reverse-phase HPLC method for the determination of genotoxic N-Nitrosamine's impurities in the Efavirenz drug substance. Methodology: The study adopted an HPLC-based quantification method at the Department of Chemistry, Acharya Nagarjuna University, Guntur, Andhra Pradesh between April 2022 and August 2022. Determination of genotoxic N-Nitrosamines in Efavirenz drug substance. N-Nitrosamine's impurities were determined by RP-HPLC method using Zorbax SB C18 (150x4.6mm, 3.5µ) column as stationary phase. Column temperature maintained 25°C, injection volume 20 µL, flow rate 1.0 mL/min and sample cooler temperature 5°C and run time was 15 minutes. The mixture of 0.1% formic acid buffer and methanol in the ratio of 50:950 (v/v) was used as the mobile phase. wavelength 240 nm. respectively. Results: There is no interference of blank at N-Nitrosamine's impurities peaks. The elution order and the retention times of impurities and Efavirenz obtained from individual standard preparations and mixed standard preparations are comparable. Six replicate injections were done for precision experiments. The peak regions of Efavirenz and its Nitrosamines were used to calculate the %RSD. The precision of the method was checked by injecting six different preparations at the specification level with respect to the test sample concentration. The % RSD for the results obtained from the method precision study was within the limit. The accuracy studies were shown as %recovery for N-Nitrosamine's impurities at the specification level. The limit of % recovered shown is in the range of 80 and 120% and the results obtained were found to be within the limits. Hence the method was found to be accurate. The technique has been validated in accordance with ICH rules, and all validation parameters meet the acceptance criteria of the ICH Q2 specification. Conclusion: An RP-HPLC method that can evaluate genotoxic Nitrosoamines in Efavirenz at trace level concentration has been devised in accordance with ICH criteria. The efficacy of the approach was guaranteed by its specificity, precision, linearity, and accuracy. Because of this, the method is suitable for the objectives it was intended to fulfill and may be effectively applied to the release testing of efavirenz into the market. The procedure is well suited to their intended functions and can be successfully implemented for the release testing of Efavirenz into the market.